2017
DOI: 10.4081/aiua.2017.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging (NBI) cystoscopy and assisted bipolar TURBT: A preliminary experience in a single centre

Abstract: Objective: The aim of this study was to compare, in order to increase our ability to detect bladder cancer, the predictive power of narrow band imaging (NBI) versus white light cystoscopy (WL). The secondary objective was to evaluate how the preoperative use of NBI cystoscopy can increase the ability to detect bladder lesions in terms of status, multi-focality and dimensions. Materials and methods: Between June 2010 and April 2012, 797 consecutive patients, 423 male and 374 female, affected by suspected bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The specificity and false positive rates in the NBI arm were superior to those of the WLI examination but were not statistically significant ( 78 ). Giulianelli et al in a comparative study, reported improved detection by the NBI arm by 30%, especially in patients with lesions smaller than 3 cm, and unifocal and recurrent lesions ( 79 ). Geavlete et al reported on their experiences in a single institute study on within-patient comparison of WLI and NBI ( 80 ).…”
Section: Resultsmentioning
confidence: 99%
“…The specificity and false positive rates in the NBI arm were superior to those of the WLI examination but were not statistically significant ( 78 ). Giulianelli et al in a comparative study, reported improved detection by the NBI arm by 30%, especially in patients with lesions smaller than 3 cm, and unifocal and recurrent lesions ( 79 ). Geavlete et al reported on their experiences in a single institute study on within-patient comparison of WLI and NBI ( 80 ).…”
Section: Resultsmentioning
confidence: 99%